Prevalence of sarcopenia in older adults in two retirement homes in Pereira, Colombia: Prevalencia de sarcopenia en adultos mayores de dos hogares geriátricos de Pereira, Colombia - Rodríguez Gutiérrez, María M. (2022)
Introduction: Is a risk factor for morbidity, mortality and disability in older adults, so its management is a priority in geriatrics. The aim of this article is to characterize a population of older adults from two geriatric homes and to establish the prevalence of sarcopenia and the degree of dependence. Methods: Cross-sectional study developed in the city of Pereira-Colombia. A population of 72 adults from 65 to 98 years of age was included, using probability sampling. Sarcopenia was determined by means of the Criteria of the European Consensus on Definition and Diagnosis of Sarcopenia, evaluating grip strength, skeletal muscle mass index, in case of sarcopenia, the severity of sarcopenia together with walking speed, and the degree of dependence according to the Barthel scale.  Results: 57 people participated. A total of 68.4% (n=39) were women. The median age was 83 years. Two percent had no sarcopenia, 9% had suspected sarcopenia, 28% had confirmed sarcopenia and 61% had severe sarcopenia. According to the Barthel scale, 31.5% were independent, 45.6% had mild, 15.8% moderate, 5.3% severe and 1.8% total dependence. Conclusions: The prevalence of sarcopenia in nursing homes in Pereira is higher compared to that reported in the literature. Similarly, being in a private nursing home does not guarantee a better physical condition and/or quality of life